Preparation, Shelf, and Eating Quality of Ready-to-Eat “Guichang” Kiwifruit: Regulation by Ethylene and 1-MCP - Yan, Han; Wang, Rui; Ji, Ning; Cao, Sen; Ma, Chao; Li, Jiangkuo; Wang, Guoli; Huang, Yaxin; Lei, Jiqing; Ba, Liangjie (Frontiers in Chemistry, 2022)
The acceptance of kiwifruit by consumers is significantly affected by its slow ripening and susceptibility to deterioration. Ready-to-eat “Guichang” kiwifruit and its preparation technology were studied by the regulation of ethylene and 1-MCP. Harvested kiwifruits were treated with 100–2000 μl L−1ethylene for 36 h (20°C) and then treatment with 0–0.5 μl L−1 1-MCP. The results showed that the preservation effect of 0.5 μl L−1 1-MCP is inefficient when the soluble solid content of kiwifruit exceeded 15%. The ethylene-treated fruits reached an “edible window” after 24 h, but a higher concentration of ethylene would not further improve ripening efficiency, while the optimal ethylene concentration was 250 μl L−1. Moreover, after 250 μl L−1 ethylene treatment, 0.5 μl L−1 1-MCP would effectively prolong the “edible window” of fruits by approximately 19 days. The volatile component variety and ester content of 0.5 μl L−1 1-MCP-treated fruits were not different from those of the CK group. Principal component analysis and hierarchical cluster analysis indicated that the eating quality of fruits treated with 0.5 μl L−1 1-MCP was similar to that of fruits treated with ethylene. Consequently, ready-to-eat “Guichang” kiwifruit preparation includes ripening with 250 μl L−1 (20°C, 36 h) ethylene without exceeding the 1-MCP threshold and then treated with 0.5 μl L−1 1-MCP (20°C, 24 h). This study highlights the first development of a facile and low-cost preparation technology for ready-to-eat “Guichang” kiwifruit, which could reduce the time for harvested kiwifruit to reach the “edible window” and prolong the “edible window” of edible kiwifruit.